MODELUL INSTRUIRII DIFERENŢIATE A STUDENŢILOR - USM ADMIN (Moldova State University, 2011)
The interest for the issues of differential teaching is aroused by the phenomenon of the higher education massification and also by the effort of the training specialists' quality improvement. In this article, a pattern of students' differential teaching is presented, in which the computer/informational technologies are used for learning content's variation, for students' production differentiation, for communication between actors in the learning process, but also for execution of an instructional scaffolding.